2016
DOI: 10.1152/advan.00001.2016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of first-year medical students’ perceptions of teaching and learning through team-based learning sessions

Abstract: Team-based learning (TBL) is an emerging teaching and learning strategy being employed in medical schools. The College of Medicine at Alfaisal University has adopted a TBL approach as an instructional method for first-year medical students. The aim of the present study was to describe the TBL method employed at Alfaisal University College of Medicine and to assess first-year medical students' perceptions of this learning modality for the anatomy- and physiology-based blocks/courses in organ systems form of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
2
24
0
2
Order By: Relevance
“…25 It was also a problem that all students tended to study with excellent academic performance students in one group. 26,27 In order to better learn from each other, discuss within and between groups, and compete, the grouping method was carefully designed as described in the method section.…”
Section: Discussionmentioning
confidence: 99%
“…25 It was also a problem that all students tended to study with excellent academic performance students in one group. 26,27 In order to better learn from each other, discuss within and between groups, and compete, the grouping method was carefully designed as described in the method section.…”
Section: Discussionmentioning
confidence: 99%
“…It was inserted by students' group discussion, cross learning and study reports, etc., which can encourage students to have more communications with teachers and other students so as to improve students' abilities of self-learning, thinking and exploring new knowledge. Therefore, sandwich learning has the advantages as team-based learning (TBL) in which inquiry teaching stimulates students' initiative study (Obad et al, 2016;Pogge, 2016;Seidel & Richards, 2001;Thomas & Bowen, 2011). The downside is that the cross-learning discussion during sandwich teaching is a bit noisy because of the large number of classes, which has a little impact on the learning effect.…”
Section: Resultsmentioning
confidence: 99%
“…The class sessions were used exclusively for the assessment and application of knowledge through case-based discussions. A growing amount of evidence from different disciplines is supported the efficacy of active learning (Antepohl & Herzig, 1999;Obad et al, 2016;Pogge, 2016;Seidel & Richards, 2001;Thomas & Bowen, 2011). Our experience in implementing a SL approach that created an appropriate active learning environment was well received, according to both student and teacher feedback.…”
Section: Sandwich Learning Is Conductive To Cultivating Student's Abimentioning
confidence: 90%
See 1 more Smart Citation
“…Although the TBL teaching method was introduced in the Middle East a few years ago, very limited studies on it are available. Only two studies have been conducted in KSA to describe the experience (13,14) both of which were at the same university (Alfaisal) in Riyadh. Although both studies reported a favourable impression by the students and the study by Anwar et al (2012) showed a correlation between TBL and improved nal exam scores, however such scores where compared between different cohorts and thus different exams.…”
mentioning
confidence: 99%